"Experts in Decolonization?" French Statebuilding and Counterinsurgency in Chad, 1969–1972. Issue 2 (3rd March 2020) - Powell, Nathaniel K.
Abstract: This article examines French efforts to save the regime of Chadian president François Tombalbaye from widespread rebellion threatening his rule. It particularly focuses on the establishment of a Mission pour la réforme administrative (MRA) led by a former French colonial governor, Pierre Lami. In conjunction with wider French military efforts, this mission aimed to re-establish state authority throughout areas of Chad affected by armed rebellion. It marked the first major postcolonial French attempt at statebuilding in its former African colonies. On the basis of MRA and French diplomatic records, this article will argue that while the French military managed to effectively defeat much of the insurgency, the MRA actually weakened the Chadian state and contributed to lasting insecurity in much of the country. This resulted from a combination of ill-fated policies aiming to empower customary local authorities over recalcitrant populations, and the creation and arming of large numbers of local militias. In the short-term this helped to undermine rebel control over remote areas, but these policies also exacerbated local-level violence, and impeded the return of state authority.